2014
DOI: 10.36457/gizindo.v32i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Kecukupan Zat Gizi Dan Perubahan Status Gizi Pasien Selama Dirawat Di Rumah Sakit Umum Pusat Sanglah Denpasar

Abstract: Malnourished in hospitalized patients was reported relatively high (30-50%). It was occurred during hospital care (iatrogenic malnutrition). It was potentially decrease the curing process, prolong length of stay, and rose up the cost of care. A prospective study was conducted in General Central Hospital of Sanglah Denpasar, included 42 male and female of hospitalized patients during period of February -Mart 2006 aged 18 to 70 years. The aim of the study was to assess the change of nutritional status index and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
0
0
2
Order By: Relevance
“…The results of this study were in line with Fayakun's research that showed there was a difference change or increase in body weight and nutritional status based on the BMI of respondents when they went home, but it was not significantly related to the length of stay in hospital (p > 0.05) [17]. This study is also in line with Weta and Wirasamadi [28] research that showed there was a change or difference in body weight and nutritional status based on BMI from the beginning of admission to hospital discharge with an average length of treatment of 6.4 days, but from the length of treatment (1-3 days), there was no significant change in body weight and BMI. The results of this study were also in line with the research by Ernawati et al [29] showing that giving a high protein milk diet could improve nutritional status of adult patients with pulmonary TB through increasing the body weight, energy, and protein intake.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study were in line with Fayakun's research that showed there was a difference change or increase in body weight and nutritional status based on the BMI of respondents when they went home, but it was not significantly related to the length of stay in hospital (p > 0.05) [17]. This study is also in line with Weta and Wirasamadi [28] research that showed there was a change or difference in body weight and nutritional status based on BMI from the beginning of admission to hospital discharge with an average length of treatment of 6.4 days, but from the length of treatment (1-3 days), there was no significant change in body weight and BMI. The results of this study were also in line with the research by Ernawati et al [29] showing that giving a high protein milk diet could improve nutritional status of adult patients with pulmonary TB through increasing the body weight, energy, and protein intake.…”
Section: Discussionsupporting
confidence: 90%
“…18 Hal tersebut selaras dengan yang dikemukakan Weta dan Wirasamadi (2009) bahwa menurunnya keadaan gizi dapat disebabkan oleh asupan zat gizi yang kurang, terjadinya gangguan gastrointestinal (mual, kembung, tidak nafsu makan), tingkat beratnya penyakit dan status gizi awal masuk rumah sakit. 19…”
Section: Bahasanunclassified
“…Kondisi tersebut menunjukkan bahwa secara umum konsumsi makanan pasien belum dapat mencukupi kebutuhan energi dan proteinnya. Lebih lanjut, penelitian yang dilakukan oleh Weta (2009) di RSUP Sanglah Denpasar menunjukkan bahwa rata-rata tingkat konsumsi energi dan protein pasien masih berada di bawah kebutuhan yaitu sebesar 78,1% untuk tingkat konsumsi energi dan 78,3% untuk tingkat konsumsi protein.…”
Section: Pendahuluanunclassified